Attrition in software companies: Reason and measures. (2022) - Pallathadka, Harikumar; Hari Leela, V.; Patil, Sushant; Rashmi, B.H.; Jain, Vipin; Ray, Samrat
Abstract: The amount of people leaving an organization plays a critical role in business success. Higher employee turnover could be serious as they are an essential part of every business. The loss of key people would have significant impacts on organizational and financial development as well as on maturity. The word "Attrition" refers to scaling down of employees in an organization. It occurs because of retirement, resignation or death of the employee. There can be many reasons for an employees to leave an organization like he may be getting higher job position in some other company or he may want to change his profession or he may leave an organization for higher studies, etc. A further contributing factor to turnover is the absence of employees' confidence in their representatives, which results in a lack of motivation and therefore in low employee retention. From the employee's side they state that lack of recognition and lack of growth within the organizations. Unfair treatment of employees is also another reason. Recently, gender discrimination has also contributed attrition. Finally, the present generation finds their jobs less challenging.